Bioassay-guided identification of anti-cholinesterase and ichthyotoxic compounds from Walsura chrysogyne (Miq.) Bakh.f.apud van steenis - Mahmod, Ilya Iryani (2012)
Phytochemical studies on Walsura chrysogyne leaves and barks have resulted in the isolation of ten compounds including two new compounds which namely chrysura (39) and 20R,24S-epoxy-25-hydroxydammaran-3-one (43). The other eight compounds are cycloart-23-ene-3α, 25-diol (35), dymalol (36), 25-methoxycycloart-23-en-3β-ol (37), eichlerianic acid (38), foveolin A (40), viridiflorol (41), cabraleadiol (42) and methyl eichlerianate (44). The structures of the isolated compounds were elucidated using spectroscopic techniques including Nuclear Magnetic Resonance (NMR), Mass Spectrometry (MS), Fourier Transform Infrared (FT-IR), X-ray crystallography and by comparison with the reported data from literatures. Based on a bioautographic Thin Layer Chromatography (TLC) profile of anti-acetylcholinesterase activity and ichthyotoxic assay, ethyl acetate fraction from leaves and hexane fraction from bark were further fractionated by several chromatographic techniques. The EtOAc-soluble part from leaves, which gave the strongest activity in ichthyotoxicity and TLC bioautography of acetylcholinesterase enzyme assay, was further fractionated and resulted in purification of six triterpenes (35, 36, 37, 38, 39 and 40). Repeated chromatography of the hexane bark fraction on normal phase silica gel led to the purification of a sesquiterpene (41) and three triterpenes (42, 43, and 44). All of the isolated compounds from leaves and barks, except for 35 and 37 which amounts are too small, were then subjected to ichthyotoxic assay at a concentration of 40 ppm each. Only eichlerianic acid (38) and viridiflorol (41) exhibited strong toxicity against zebrafish (Danio rerio). The median tolerance limit (TLM = IC50) for 39 and 41 was evaluated by straight line graphical interpolation and resulted in the values of 6.7 and 15 ppm respectively. Compound 36, 38, 39 and 41 showed positive result on TLC-bioautography with fast blue B salt. However, the obtained IC50 for them by using Ellman’s method was not significant (>200 μg/ml).